Challenges to the Implementation of the Common Core Programme JHS English Curriculum: A Case of Tumu Municipality - Kanluoru, Rahinatu Dauda; Zinteng, James; Ana, Paul Gbolo Ni; Fuseini, Miftawu (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
The research was conducted in the Tumu Municipality. The study looked into the concerns teachers had regarding the JHS Common Core Programme (CCP). Government training sessions for Junior High School (JHS) teachers on the common core programme English language curriculum (CCPEC) were criticized for lacking the instructional resources and friendly environment needed for a successful rollout. The study used a descriptive research design and a quantitative approach to gather information from English language teachers and head teachers in public Junior High Schools' (JHSs). The results of the study show that teachers had difficulties when putting the Common Core Programme into practice. They expressed interest in useful evaluation techniques, realizing the importance of assessing students' skills outside of the box. The study highlights the value of monitoring and assessment even in the face of budgetary limitations. In conclusion, addressing these issues requires fostering a collaborative school culture to ensure the successful implementation of the Common Core Programme English curriculum in Ghana. The study suggests the conduct of a longitudinal study to examine the long-term effect of the implementation of the Common Core Programme JHS English curriculum.
Keywords: Challenges; Implementation; Common core curriculum; Pedagogical concerns; Educational system